New host of phytoplasmas in Cuba - Zamora, Loidy; Quiñones, Madelaine L.; Piñol, Bertha; Acosta, Karell L. (Revista de Protección Vegetal, 2014)
Plant-pathogenic phytoplasmas are wall-less bacteria of the class Mollicutes with a small genome size. They are pathogens that can cause devastating losses in crops and natural ecosystems worldwide. The phytoplasmas are phloem-limited bacteria that can be transmitted by phloem-feeding insects of the Hemiptera order. In common bean (Phaseolus vulgaris L.) plantations of the province of Mayabeque, plants of Cyperus rotundus L. (known as coco-grass, Java grass, nut grass, purple nut sedge, red nut sedge, Khmer kravanh chruk) without symptoms were found and carried to the laboratory to be molecularly analyzed for phytoplasma infections. Phytoplasmas were detected in these plants, and it was considered to be a potential risk for the common bean crop. Weeds harbor a rich insect fauna, such as leafhoppers, plant hoppers and psyllids, some of which have the capacity to transmit phytoplasmas, wich were the three percent of the pathogens causing emerging infectious diseases (EIDs) of plants in 2004. For these reasons, in addition to the fact that the climate change can produce different behavior in these infectious diseases and in the distribution pattern of the insect vectors as well, research on this topic should be continued.